2019
DOI: 10.3344/kjp.2019.32.4.245
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell therapy in pain medicine

Abstract: Stem cells are attracting attention as a key element in future medicine, satisfying the desire to live a healthier life with the possibility that they can regenerate tissue damaged or degenerated by disease or aging. Stem cells are defined as undifferentiated cells that have the ability to replicate and differentiate themselves into various tissues cells. Stem cells, commonly encountered in clinical or preclinical stages, are largely classified into embryonic, adult, and induced pluripotent stem cells. Recentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 115 publications
0
21
0
Order By: Relevance
“…Recently, mesenchymal stem cells (MSCs)have been widely applied to the treatment of pain as an alternative or promising treatment for severe osteoarthritis, neuropathic pain, and intractable musculoskeletal pain which are ineffective to traditional drugs [15]. In several preclinical studies, have confirmed that MSC have a role in neuroprotective and axonal growth stimulation in various models of nervous system injury [16,17], In a number of preclinical and clinical studies, intraarticular injections (IA) of MSCs can relieve pain and improve function [18].…”
Section: Researchmentioning
confidence: 99%
“…Recently, mesenchymal stem cells (MSCs)have been widely applied to the treatment of pain as an alternative or promising treatment for severe osteoarthritis, neuropathic pain, and intractable musculoskeletal pain which are ineffective to traditional drugs [15]. In several preclinical studies, have confirmed that MSC have a role in neuroprotective and axonal growth stimulation in various models of nervous system injury [16,17], In a number of preclinical and clinical studies, intraarticular injections (IA) of MSCs can relieve pain and improve function [18].…”
Section: Researchmentioning
confidence: 99%
“…Although categorized as chronic pain, neuropathic pain is regarded as a debilitating disease process (Fortino et al, 2013; Vadivelu et al, 2013). As the pathogenesis is very complicated, the treatment of neuropathic pain remains a challenge (Han et al, 2019). Growing evidence suggests that neuroinflammation originally serves to promote the healing of peripheral nerve injuries and diseases.…”
Section: Introductionmentioning
confidence: 99%
“…13 Interestingly, IL-33/ST2 may promote gut mucosal healing through increasing the expression of miRNA-320 in colitic mice during the recovery period, which facilitates the epithelial restitution and the inflammation resolution. 14 Recently, it has been documented that neuropathic pain induced by nerve injury can be relieved by delivering bone marrow stromal cells (BMSCs) locally, intrathecally, or systematically (see reviews: Fortino et al, 15 Huh et al, 16 Han et al 17 ). However, detailed mechanisms underlying the genesis and maintenance of neuropathic pain, as well as its stem cell-based therapeutic intervention remained not entirely clear.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been documented that neuropathic pain induced by nerve injury can be relieved by delivering bone marrow stromal cells (BMSCs) locally, intrathecally, or systematically (see reviews: Fortino et al., 15 Huh et al., 16 Han et al. 17 ). However, detailed mechanisms underlying the genesis and maintenance of neuropathic pain, as well as its stem cell-based therapeutic intervention remained not entirely clear.…”
Section: Introductionmentioning
confidence: 99%